Pengaruh Latihan Kekuatan Otot Lengan Terhadap Kemampuan Servis Bawah Bola Voli Pada Ekstrakurikuler Di SMPN 3 Kota Bengkulu - Anjeli Lastavia; Megi Personi; Mariska Febrianti (Educative Sportive, 2026)
This study aims to determine the effect of arm muscle strength training on volleyball underhand serve ability in extracurricular activities for students at SMPN 3 Bengkulu City. A total sampling method was used to determine the number of respondents, resulting in 13 volleyball students from SMPN 3 Bengkulu City This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design that includes a pretest (test before treatment) and a posttest (test after treatment) within one group. Data collection used test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of arm muscle strength training on volleyball underhand serve ability in extracurricular activities for students at SMPN 3 Bengkulu City, with a calculated t-value of 9.890 and a t-table value of 1.782, with a significance level of α = 0.05 and dk = 13.